Relationship between epidemiologic surveillance with geo-climatic variables during Zika outbreak in Guerrero State, Mexico 2016 - Jimenez-Alejo, Abel; Zárate-Nahón, Ewry A.; Sampedro-Rosas, María L.; García-Ibáñez, Sergio; Rosas-Acevedo, José L. (International Journal Of Community Medicine And Public Health, 2018)
Background: Zika like dengue and chikungunya represent public health problems. Cases of ZIKV infection are emerging in the Americas, from Argentina spread until Brazil and Colombia, later entry to Mexico and managed to establish itself in most of the states. Methods: The cases (2016-2017) of epidemiological surveillance of the first outbreak of Zika in Guerrero were used. The incidence rates (IR) for each municipality were estimated (cases/100 000 inhabitants) to develop the first maps at the municipal and state level; which aimed to explore the relationship between Zika cases and geo-climatic variables. Results: At January 3, 2017 in Guerrero State [epidemiological week (SE) 52 of the year 2016] were reported 861 confirmed ZIKV cases (10.06% of total registered cases at federal level). Guerrero State it was placed within the six states with the largest number of cases: Veracruz (1967), Yucatan (1284), Nuevo Leon (844), Chiapas (804) and Oaxaca (507); concentrated 73.26% (6 267/8 554) of the country’s cases. In this study we identified the geo-environmental factors associated with ZIKV occurrence in each municipality of the Guerrero State: very high rain (1201-1460 mm), low elevation (2-398 masl) and high population density (≥62071 inhabitants/km2). Conclusions: This study represents the first approach to Zika outbreak in Guerrero State. Although tests of spatial nature are not presented; the maps presented show how the characteristics by region have high influence and that the most affected areas were the coastal areas: Acapulco, Small Coast and Big Coast.